From civil to political religion : the intersection of culture, religion and politics - Cristi, Marcela, 1940- (Wilfrid Laurier University Press, 2001)
A critique of the civil religion thesis, identifying the most basic deficiencies of literature on this topic. An informative case study of civil religion in Pinochet's Chile substantiates the critique.